(untitled) (Global Journal of Science Frontier Research, 2021)
This study assessed the effects of climate variability on Maize yield in Wukari Local Government Area of Taraba State between 1999 and 2018. The research design employed in the study was an ex-post facto and analytical design. Hence, the study is a quantitative study that provides statistical data as empirical evidence and produces descriptive and informative sceneries of the topic study. Based on the objectives of this study and data analysis, the results revealed an increasing trend in average annual maximum temperature in the study area, with 62 percent variability, and a deceasing trend in average annual minimum temperature, with 44 percent variability. More so, the results revealed an almost uniform but increasing trend in average annual rainfall in the study area between 1999 and 2018, with a 37 percent variability. Furthermore, results of the trend analysis revealed an increasing trend in maize yield in the study area, with 50 percent variability. The correlation analysis revealed a non-statistically significant strong positive linear relationship (r = 0.088, sig. 0.712 > 0.05) between the average rainfall and average temperature in the study area.